Transisi Kurikulum 2013 Menjadi Kurikulum Merdeka: Peran dan Tantangan dalam Lembaga Pendidikan - Nurul Qomariyah; Muliatul Maghfiroh (UIN Sunan Gunung Djati Bandung, 2022)
Education after the COVID-19 pandemic in Indonesia must experience recovery and be able to overcome the learning crisis by improving the quality of education. The Ministry of Education, Culture, Research and Technology (Kemendikbudristek) announces the relevant strategies for the restoration of education and its implications for the future. The government is preparing a transition from 2013 Curriculum simplification to an Independent curriculum. The purpose of this study is to first analyze the transition to the free learning curriculum as a new form of innovation in the recovery of education after the COVID-19 pandemic. Second, the role and challenges of educational institutions in applying the independent learning curriculum. The research method and approach used is library research. The results of this study indicate that first, the simplification of the 2013 curriculum into an independent curriculum can mitigate the learning loss experienced by the 2013 curriculum during the pandemic. This has strengthened the minister of education, Nadiem Makarim, in changing the design and strategy of a more comprehensive curriculum, namely the 2013 curriculum, followed by the emergency curriculum and then the independent curriculum. Second, the role of educational institutions is given full freedom of curriculum options to be implemented. In the next two years, the curriculum transition will be carried out in stages until it reaches the 2024 National curriculum with a three-year gap for schools to adapt to an independent curriculum. Meanwhile, the challenge for educational institutions is to implement an independent curriculum through systematic and gradual changes to transform education as the main goal of achieving an independent learning curriculum.